Atomic-scale investigation of the heterogeneous structure and ionic distribution in an ionic liquid using scanning transmission electron microscopy. Issue 19 (4th April 2019) - Sugimori, Yuki; Miyata, Tomohiro; Hashiguchi, Hiroki; Okunishi, Eiji; Mizoguchi, Teruyasu
Abstract : Ionic liquids show characteristic properties derived from being composed of only molecular ions. The numbers of all constituent molecules and ions were quantitatively estimated from the image intensity and the origin of the heterogeneity in the ionic liquid was discussed. Abstract : Ionic liquids show characteristic properties derived from them being composed of only molecular ions, and have recently been used as solvents for chemical reactions and as electrolytes for electrochemical devices. The liquid structures, i.e., ionic distributions, form when solutes are dissolved in ionic liquids and fundamentally affect the reactions and transfer efficiency in such solutions. In this study, we directly observe the liquid structure in a solution of the long-chain ionic liquid 1-octyl-3-methylimidazolium bromide (C8 mim Br) and barium stearate (Ba(C17 H35 COO)2 ) using the annular dark-field method of scanning transmission electron microscopy (ADF-STEM). The ADF image shows a 10 nm-scale heterogeneity in the image intensity, which reflects the heterogeneous ionic distribution in the solution. The number density distributions of all the component ions (C8 mim +, Br −, Ba 2+, and C17 H35 COO − ) were estimated from the ADF image intensity and then visualized. These ionic distribution maps depicted the spatial relationships between the ions at the sub-nanometer scale and revealed that the heterogeneity is largely derived from the large differences in size, charge distributions, and van der Waals interactions.